KERANGKA HUKUM UNTUK PENGEMBANGAN HIDROGEN HIJAU DI INDONESIA: ANALISIS REGULASI DAN KEBIJAKAN FISKAL - Lya Kartika Sari (Fakultas Hukum Universitas Sebelas Maret, 2025)
In recent years, Indonesia has taken major steps in the energy transition to achieve the Net Zero Emission (NZE) target by 2060, one of which is developing green hydrogen. This article analyzes the legal framework that supports investment in green hydrogen technology in Indonesia, focusing on regulations and fiscal policies. The findings of the article indicate that although the existing regulatory framework is supportive, the implementation of green hydrogen development and fiscal policies still faces challenges. This article concludes that to accelerate the development of green hydrogen, optimization of regulations and fiscal policies is necessary.